Saberes e relatos docentes sobre a pré-escola: entre o lúdico e a reinvenção da aprendizagem - Araújo, Wagnês Barbosa de (2023)
Teaching work with play in pre-school Early Childhood Education is crossed the challenges of schooling and, at the same time, providing opportunities for interact and play, adding knowledge aimed at development children’s cognitive skills in favor of meaningful learning. The balance betwee playing and learning are not always considered, mainly because there is a pedagogical tendency to minimize playing time in favor of educational activities reproduction that only aim to equip writing skills. Such a vision reductive approach does not recognize the contributions of play to the advancement of intelligence childish. In this sense, there is an emerging need to point out the role of play in preschool learning, starting this trajectory through the reconfiguration of teaching knowledge. Defending learning through play therefore permeates the objective main focus of this research in order to highlight the importance of play in preschool as a path to meaningful learning, starting from training teacher as the driving force behind this knowledge. Thus, the theoretical framework to deepen this purpose, it seeks support in Piaget's studies (2020), Vygotsky (2007) and Luckesi (2002, 2004), among other authors. In reference of to pedagogical training for the appropriation of playfulness in educational spaces are adopted the references of Imbernón (2011, 2009), Tardif (2014), Nóvoa (1999, 1913), Freire (1996,1997, 2016), Morin (2000, 2021), among others, who deal with the teaching professionals in their pedagogical missions, praising the person of the teacher in his human challenges. The methodology starts from an approach qualitative approach approaching techniques from action research and character investigations ethnographic with the support of participant observation and semi-structured interviews, considering the content of the narratives and their meanings for understanding the pedagogical processes related to childhood. The research field involves the Nursery and Pre-School Prof.ª. Socorro de Fátima Cavalcante Viana, located in Remígio-PB. The study is based on the premise that the appropriation of play in the sphere teacher can increase the quality of pedagogical practices and contribute to a meaningful learning in preschool. In terms of educational product, they will be pedagogical training workshops for recreational activities were implemented. The dimensions theoretical-practical, with regard to insertion in the context studied with interventions that propose educational changes, presente possibilities for advancement in Pre-School teaching, contributing to the researched reality and the Community school, through the knowledge of collaborating teachers.